Attitudes of Community Pharmacy Service Users towards Vaccination Programs in Pharmacy: A Cross-Sectional Survey-Based Study in Croatia - Doris Rusic; Doris Nanasi; Josko Bozic; Anamarija Jurcev Savicevic; Dario Leskur; Ana Seselja Perisin; Darko Modun; Marino Vilovic; Josipa Bukic (MDPI AG, 2022)
Background: The aim of this study was to explore community pharmacy service users' attitudes and opinions towards vaccination programs in pharmacy conducted by a doctor of medicine or a pharmacist. Methods: The questionnaire used in this study comprised 40 items about demographics, sources of information, attitudes about vaccination, attitudes about vaccination in community pharmacies, and willingness to pay for such a service. Results: A total of 385 people participated in this study. Injection was the preferred route of administration of vaccine for more than half of study participants (50.6%). Univariate analysis showed that those who had a healthcare worker as a family member and those familiar with the HPV vaccine had better attitudes; however, those results were no longer significant after factoring in other variables in multivariate analysis. More than half (59.2%) of the study population would consider vaccination service in community pharmacies only if it were free or covered by the national health insurance. Conclusions: More than half of the participants believed that providing vaccination services in community pharmacies would result in greater vaccination rates for seasonal illnesses. However, around half would prefer that it were conducted exclusively by a physician. Less than 10% of the study participants would pay out of their pocket for such a service.